Variabilité spatiotemporelle des températures aux échelles fines dans le vignoble de Vinho verde (Portugal) dans un contexte de changement climatique - Quénol, Hervé (2007)
In the Entre Douro e Minho area (North of Portugal), an agroclimatologic study is made in two distant soils of wine of a few kilometres and from which the topographic characteristics and the variety of vine are different. A climatic study on fine scales is carried out in order to determine the local influence of the surface characteristics on the weather parameters. The temperature measurements and the agronomic analysis carried out between February and April 2003 showed a strong space-time variability of the spring frost risk between the two sites and inside even of the soils. In a context of climate change, this type of climatic study in fine scales must be taken into account to ameliorate simulation and predictions.